EML4-ALK fusion variant V3 is a high-risk feature conferring accelerated metastatic spread, early treatment failure and worse overall survival in ALK+ non-small cell lung cancer - Christopoulos, Petros; Endris, Volker; Bozorgmehr, Farastuk; El Sayed, Mei; Kirchner, Martina; Ristau, Jonas; Buchhalter, Ivo; Penzel, Roland; Herth, Felix; Heußel, Claus Peter; Eichhorn, Martin E.; Muley, Thomas; et al. (International journal of cancer, 2018)
In order to identify anaplastic lymphoma kinase-driven non-small cell lung cancer (ALK+ NSCLC) patients with a worse outcome, who might require alternative therapeutic approaches, we retrospectively analyzed all stage IV cases treated at our institutions with one of the main echinoderm microtubule-associated protein-like 4 (EML4)-ALK fusion variants V1, V2 and V3 as detected by next-generation sequencing or reverse transcription-polymerase chain reaction (n = 67). Progression under tyrosine kinase inhibitor (TKI) treatment was evaluated both according to Response Evaluation Criteria in Solid Tumors (RECIST) and by the need to change systemic therapy. EML4-ALK fusion variants V1, V2 and V3 were found in 39%, 10% and 51% of cases, respectively. Patients with V3-driven tumors had more metastatic sites at diagnosis than cases with the V1 and V2 variants (mean 3.3 vs. 1.9 and 1.6, p = 0.005), which suggests increased disease aggressiveness. Furthermore, V3-positive status was associated with earlier failure after treatment with first and second-generation ALK TKI (median progression-free survival [PFS] by RECIST in the first line 7.3 vs. 39.3 months, p = 0.01), platinum-based combination chemotherapy (median PFS 5.4 vs. 15.2 months for the first line, p = 0.008) and cerebral radiotherapy (median brain PFS 6.1 months vs. not reached for cerebral radiotherapy during first-line treatment, p = 0.028), and with inferior overall survival (39.8 vs. 59.6 months in median, p = 0.017). Thus, EML4-ALK fusion variant V3 is a high-risk feature for ALK+ NSCLC. Determination of V3 status should be considered as part of the initial workup for this entity in order to select patients for more aggressive surveillance and treatment strategies.
First published: 24 January 2018
Gesehen am 14.05.2019